Materials for electrochemical ammonia synthesis. Issue 5 (19th December 2018) - McPherson, Ian James; Sudmeier, Tim; Fellowes, Joshua; Tsang, Shik Chi Edman
Abstract : Direct electrochemical synthesis of ammonia is proposed as a means of reducing the carbon footprint of the fertiliser industry, as well as providing new opportunities for carbon-free liquid energy storage. Abstract : Direct electrochemical synthesis of ammonia is proposed as a means of reducing the carbon footprint of the fertiliser industry, as well as providing new opportunities for carbon-free liquid energy storage. We review the current status of research into materials for electrochemical ammonia synthesis and evaluate the reported rates and efficiencies in terms of recent US Department of Energy targets. Surprisingly, development of electrocatalysts has only recently received much attention, and despite a number of promising rates, the target values remain distant. A number of theoretical studies suggest a range of candidate materials yet to be explored.